Code Switching in the Social Media Era: A Linguistic Analysis of Instagram and TikTok Users - Sholihatul Hamidah Daulay; Ahmad Husein Nst; Fitri Randia Ningsih; Hotma Berutu; Novia Robeitah Irham; Rifaatul Mahmudah (LPPM Universitas Bumigora Mataram, 2024)
The phenomenon of code-switching nowadays is very often encountered in both direct and indirect communication or on social media. This research aims to analyze code-switching of comments on Instagram and TikTok applications. This study used qualitative as the research methodology, the type of methodology in this study used was content analysis. The data source used is the screenshots results of users’ comments on Instagram and TikTok applications. The researchers watched videos on Instagram and TikTok and read the comment attached in it. Findings after doing the analysis researcher considers there are three kinds of form code-switching that found on Instagram and TikTok account users, they are: tag-switching, intersentential code-switching, and intra-sentential code-switching. Following the type-based analysis, the researcher discovered that there are four reasons why code-switching occurs: shifting the subject, vocabulary deficit, bilingualism/multilingualism, prestige, and trend.